THE APPLICATION OF BIOEDUTAINMENT â€œFOOD FIGHT GAMEâ€ STRATEGY ON ECOSYSTEM MATERIAL TOWARDS THE LEARNING RESULT OF THE 7TH GRADERS OF JUNIOR HIGH SCHOOL - Hidayah, Koriatul; Iswari, Retno Sri; Pribadi, Tyas Agung (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ This research aimed to analyze the implementation of the â€œFood Fight Gameâ€ Bioedutainment strategy on studentâ€™s learning achievement and studentâ€™s learning activities in ecosystem teaching material. The type of the research was Nonequivalent Control Group in a Quasi Experimental Design. The population in this research was all students of VII class at SMP Negeri 18 Semarang, and VII D class was treated as experimental class and VII C as control class. To collect data of students learning achivement a test was performed whereas student learning activities were collected by observation. Questionare was used to collect data of student response to the implementation of the â€œFood Fight Gameâ€ Bioedutainment strategy. The t-test has rejected H0 at Î± = 5 %. T-test result showed that there was a significant difference between both groups. The average of student activities in the experimental class achieved 79% while the control group was only 72%. The conclusion of this research was that implementation of strategy Bioedutainment using Food Fight Game had a positive effect on studentâ€™s learning achievement and student learning activities.